Estimation of maternal and child mortality one year after user-fee elimination: an impact evaluation and modelling study in Burkina Faso - Mira Johri; Valéry Ridde; Rolf Heinmüller; Slim Haddad (The World Health Organization, 2014)
Objective To estimate the impact on maternal and child mortality after eliminating user fees for pregnant women and for children less than five years of age in Burkina Faso. Methods Two health districts in the Sahel region eliminated user fees for facility deliveries and curative consultations for children in September 2008. To compare health-care coverage before and after this change, we used interrupted time series, propensity scores and three independent data sources. Coverage changes were assessed for four variables: women giving birth at a health facility, and children aged 1 to 59 months receiving oral rehydration salts for diarrhoea, antibiotics for pneumonia and artemesinin for malaria. We modelled the mortality impact of coverage changes in the Lives Saved Tool using several scenarios. Findings Coverage increased for all variables, however, the increase was not statistically significant for antibiotics for pneumonia. For estimated mortality impact, the intervention saved approximately 593 (estimate range 168-1060) children's lives in both districts during the first year. This lowered the estimated under-five mortality rate from 235 deaths per 1000 live births in 2008 to 210 (estimate range 189-228) in 2009. If a similar intervention were to be introduced nationwide, 14 000 to 19 000 (estimate range 4000-28 000) children's lives could be saved annually. Maternal mortality showed a modest decrease in all scenarios. Conclusion In this setting, eliminating user fees increased use of health services and may have contributed to reduced child mortality.